Emulsion stabilizing properties of citrus pectin and its interactions with conventional emulsifiers in oil-in-water emulsions. (December 2018) - Verkempinck, S.H.E.; Kyomugasho, C.; Salvia-Trujillo, L.; Denis, S.; Bourgeois, M.; Van Loey, A.M.; Hendrickx, M.E.; Grauwet, T.
Abstract: The present work focused on the (i) physical characterization of the emulsion stabilizing potential of citrus pectin (CP) with different degree of methylesterification (DM; CP82, CP38 and CP10) and (ii) evaluation of interactions that occur between CP and conventional emulsifiers (Tween80 and phosphatidylcholine) used for emulsion stabilization. Firstly, the emulsifying properties of different samples were studied by evaluating the electrical charge, hydrodynamic radius, adsorbed layer thickness and change in interfacial tension. The results showed that the pectin charge was strongly dependent on its DM and pH of the aqueous phase. For example, the hydrodynamic volume and adsorbed layer thickness of CP10 were larger compared to CP38 and CP82 at neutral pH due to the presence of more chargeable carboxylic groups. Moreover, it was quantitatively shown that CP is capable of reducing the interfacial tension of an oil droplet regardless its DM, evidencing its adsorption at the oil-water interfaces and surface active properties. Secondly, the physicochemical stability of oil-in-water emulsions was evaluated during short-term storage at 4 °C. All pectin-emulsions showed the formation of a cream layer after one day. However, the nature and extent of this layer depended on the emulsion composition. All pectin single-emulsifier stabilized emulsions presented a cream layer most likely caused by bridging flocculation induced by the pectin structures. Contrastingly, depletion flocculation was observed in case of the multiple-emulsifier stabilized emulsions. In all cases, the destabilization phenomena observed were reversible as the particle size did not dramatically change over storage time, showing that CP has emulsion stabilizing potential. Graphical abstract: Highlights: Citrus pectin is a surface-active molecule. Addition of citrus pectin allows creation of emulsions with small droplet sizes. Pectin structure influences its organization at the oil droplet surface. Emulsion acidity determines the way pectin stabilizes the oil droplet interface. Combination of pectin and conventional emulsifier led to depletion flocculation.